Designing Patient-Reported Measures of Fertility: Cognitive Interview Findings from Adolescents and Young Adults with Cancer. - Canzona, Mollie Rose; Victorson, David E.; Murphy, Karly M.; Clayman, Marla L.; Reeve, Bryce B.; Patel, Bonnie; Strahley, Ashley E.; McLean, Thomas W.; Harry, Onengiya; Roth, Michael E.; Smith, Regina V.; Salsman, John M. (Journal of Adolescent & Young Adult Oncology, 2025)
Purpose: Fertility concerns (FC) are central to the well-being of many adolescent and young adult (AYA) cancer survivors. Clinical conversations about FC and fertility preservation are suboptimal, increasing patient distress. The goal of this project was to establish content validity and comprehensibility of self-report questions on FCs for AYAs with cancer. Methods: Following best practices, we conducted: (1) item identification, refinement, and generation; (2) translatability and reading level review; and (3) cognitive interviews. Items were reviewed by five AYAs in each round of cognitive interviews. Results: A systematic search yielded 63 measures and 873 items. Fifty items were subsequently modified to enhance clarity and relevance, representing subdomains of psychological and social/relational FC. Flesch–Kincaid analysis found 31 items written above the 6th grade level, which were subsequently revised. Translatability review resulted in the modification of 3 items. During cognitive interviews, 76% of AYAs found items easy to answer with 52% describing them as "very easy" and 24% as "somewhat easy." Sixty percent of participants indicated the items captured their experiences. The majority of those who reported items only somewhat reflected or did not reflect their experiences suggested items were simply not applicable for their particular case. Conclusion: This study is a critical step toward the foundation for an FC measurement system that is reliable, flexible, developmentally appropriate, comprehensible, translatable, and interpretable. Subsequent steps include psychometric testing to examine the construct validity and reliability of the FC items and calibration to enable the application of computer-adaptive testing and short form development. The evaluation will include potential item response bias by age range, gender identity, and race/ethnicity.